Neuroinformatics for Neuropsychology - Jagaroo, Vinoth. (Springer US, 2009)
Neuroinformatics for Neuropsychology Vinoth Jagaroo Emerson College and Boston University School of Medicine, Boston, MA, USA Bioinformatics involves specialized application of computer technology to investigative and conceptual problems in biology and medicine; neuroinformatics (NI) is the practice of bioinformatics in the neurosciences. Over the past two decades the biomedical sciences have been revolutionized by databases, data mining and data modeling techniques. The Human Genome Project, which depended on informatics methods, has been the most well recognized bioinformatics undertaking. Bioinformatics has since been applied all across biology and medicine, and has also transformed almost every avenue in neuroscience. Yet in neuropsychology, NI perspectives remain largely unrealized. Ironically, NI offers enormous potential to the essential praxis of neuropsychology - assessing cognitive behavior and relating cognition to neural systems. Neuroinformatics can be applied to neuropsychology as richly as it has been applied across the neurosciences. Neuroinformatics for Neuropsychology is the first book to explain the relevance and value of NI to neuropsychology. It systematically describes NI tools, applications and models that can enhance the efforts of neuropsychologists. It also describes the implications of NI for neuropsychology in the 21st century fundamental shifts away from the conventional modes of research, practice and communication that have thus far characterized the field. One of the foremost experts on the subject: Illustrates the vital role NI is playing throughout the neurosciences. Provides a sampling of NI tools and applications in neuroscience research, and lays out current organization structures that support NI. Describes the lack of NI in neuropsychology, differentiates between NI systems for neuropsychology and conventional computerized assessment methods, and proposes criteria for neuropsychology-specific NI systems. Describes NI applications and models currently in use in neuropsychology, and NI models for neuropsychology that are being pioneered in phenomics research. Discusses potential obstacles and aids to NI in neuropsychology, including issues such as data sharing, standardization of methods, and data ontology. Projects the future of neuropsychological research and practice in light of the new generation of the internet, Web 2.0, geared to collective knowledge building. A vital introduction to a profound technological practice, Neuroinformatics for Neuropsychology is important reading for clinical neuropsychologists, cognitive neuroscientists, behavioral neurologists, and speech-language pathologists. Researchers, clinicians, and graduate students interested in informatics for the brain-behavioral sciences will especially welcome this unique volume.